"You Say Praise, I Say Encouragement" - Negotiating Positive Behavior Support in a Constructivist Preschool - Victoria Carr; Mary Boat (Athens Institute for Education and Research, 2019)
A participatory action research study conducted at the Arlitt Child Development Center, a laboratory preschool at the University of Cincinnati, used naturalistic inquiry to create a solution for addressing challenging behaviors within an early childhood developmental and constructivist framework. In focus groups facilitated by a school psychology doctoral student, the center's preschool teachers created constructivist strategies for addressing a Tier I Positive Behavior Intervention and Support (PBIS) framework that was based on Response to Intervention (RTI) processes. The aim was to assess the dissonance between behavioral and constructivist approaches to early childhood interventions, often most evident in teacher language used and the emphases on reinforcement strategies in behaviorist literature. Researchers employed eco-constructivism, a philosophical perspective for addressing challenging behaviors that emerge within the ecology of the classroom, to interpret teachers' responses that were oriented toward fostering children's self-regulation skills and child agency. Findings indicate that an eco-constructivist approach to PBIS may serve as a model for blended practices in early childhood programs.